Evaluation of the fundamental technical aspects of the game in Six Nations Rugby - Esposito, G. (Journal of Physical Education and Sport, 2024)
Background: The Six Nations represents the oldest and most famous rugby tournament in the world. The several types running, of technical and of tactical in the team sports such as rugby, basketball, and soccer, vary according to physical characteristics and sports. In particular, in the rugby the running is characterized by continuous acceleration and deceleration phases, which entail a greater physical and mental commitment. Aim: The aim of this study has been of analyzed and comparison, through the video analysis, the quality of the play of the six rugby teams that participated at tournament of the Six Nations 2018 and the impact that these aspects had on the final result. Methods: The data sample is represented by the matches played and from the technical variables detected the video analysis of the matches examined. Results: The findings of this study offer valuable insights for coaches aiming to optimize training and tailor the training load based on both gender and young players. This optimization pertains to the development of coordination and conditioning skills, as well as the technical and tactical experiences of the players. Therefore, it is imperative to assess and continually monitor training, incorporating tools such as video analysis and GPS, to analyze technical and tactical aspects. This approach is a crucial element in performance control. Conclusions: The Irish national team managed to emerge thanks to the high number of passes made, a remarkable technical precision and a superior team organization of the team which allowed them to reach 26% of the goals in the tournament, underscoring that the effectiveness of ball movement in isolation does not ensure victory.